2016
DOI: 10.2147/mnm.s96916
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases in cystic fibrosis: pathophysiologic and therapeutic perspectives

Abstract: Cystic fibrosis (CF) is the most common inherited disease in the Caucasian population. CF is caused by loss-of-function mutations in the CFTR gene leading to an altered electrolyte and water movement into the airway surface liquid, dehydration of the mucus layer, defective mucociliary clearance, and increased susceptibility to airway bacterial infections. CF is characterized by airway neutrophilic inflammation and activation of airway epithelial cells leading to increased airway levels of various matrix metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…MMP3, a stromelysin produced by fibroblasts and myofibroblasts, is proficient at breaking down basal lamina proteins, proteoglycans, E-cadherin, plasminogen, interleukin (IL)-1β, and chemokine 7 [28]. The MMP3 rs3025058 is an upstream transcript variant that introduces an insertion (6A)/deletion (5A) variability at position −1612 within the promoter region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP3, a stromelysin produced by fibroblasts and myofibroblasts, is proficient at breaking down basal lamina proteins, proteoglycans, E-cadherin, plasminogen, interleukin (IL)-1β, and chemokine 7 [28]. The MMP3 rs3025058 is an upstream transcript variant that introduces an insertion (6A)/deletion (5A) variability at position −1612 within the promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9, known as neutrophil gelatinase, is produced by epithelium, fibroblasts, and leukocytes, and is capable of degrading elastin, type IV collagen, other basal lamina proteins, gelatins, tumor growth factor (TGF)-β, IL-8, and α1-antitrypsin [28]. The MMP9 rs3918242 polymorphism represents a single nucleotide variation (SNV) resulting in a C to T substitution at position −1561 in the promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…MMP‐9 is a protease produced mostly by PMNs and acts in many ways, especially by degrading components of the extracellular matrix. Its role in the CF lung disease is well described and it has a dramatic increase during episodes of pulmonary exacerbations 31–34 . The knowledge about the role of MMP‐9 in UAW disorders is recent.…”
Section: Discussionmentioning
confidence: 99%
“…Its role in the CF lung disease is well described and it has a dramatic increase during episodes of pulmonary exacerbations. [31][32][33][34] The knowledge about the role of MMP-9 in UAW disorders is recent. A study showed increased MMP-9 expression in the bone and in the mucosa of patients with CRS and osteitis, despite intranasal and postoperative use of steroids, suggesting a role of MMP-9 in the pathogenesis of osteitis.…”
Section: Discussionmentioning
confidence: 99%